2021
DOI: 10.3390/ijms22168912
|View full text |Cite
|
Sign up to set email alerts
|

Possible Use of Phytochemicals for Recovery from COVID-19-Induced Anosmia and Ageusia

Abstract: The year 2020 became the year of the outbreak of coronavirus, SARS-CoV-2, which escalated into a worldwide pandemic and continued into 2021. One of the unique symptoms of the SARS-CoV-2 disease, COVID-19, is the loss of chemical senses, i.e., smell and taste. Smell training is one of the methods used in facilitating recovery of the olfactory sense, and it uses essential oils of lemon, rose, clove, and eucalyptus. These essential oils were not selected based on their chemical constituents. Although scientific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 480 publications
(590 reference statements)
0
52
0
5
Order By: Relevance
“…Due to its therapeutic uses, carnation is nominated as a candidate for the management of COVID-19. [27][28][29][30] During the COVID-19 pandemic, the consumption of carnation as an additive to food or drink to relieve throat pain has increased. 31 A randomized clinical trial of a blend that contains carnation buds demonstrated a boost in energy levels among post-COVID-19 female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its therapeutic uses, carnation is nominated as a candidate for the management of COVID-19. [27][28][29][30] During the COVID-19 pandemic, the consumption of carnation as an additive to food or drink to relieve throat pain has increased. 31 A randomized clinical trial of a blend that contains carnation buds demonstrated a boost in energy levels among post-COVID-19 female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, flavonoids are well-known for their diverse antiviral effects, and numerous studies have also examined their effect on SARS-CoV-2. Some of these approaches are to increase their bioavailability, and thus, improve their therapeutic efficacy (Ngwa et al, 2020) while others explore the possible use of flavonoids on recovery from COVID-19-Induced anosmia and ageusia (Koyama et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It was among the major constituents in the essential oil from lemon leaf in a study by Klimek-Szczykutowicz et al (2020) . Lemon contains many chemical compounds with anti-inflammatory effects: β -caryophyllene, geraniol, limonene, linalool, myrcene, α -pinene, β -pinene, (E)- β -ocimene, sabinene, γ -terpinene, and terpinen-4-ol ( Koyama et al, 2021 for review). The high percentage of limonene suggests that the anti-inflammatory effects could be mediated mainly by limonene, but the large number of chemical constituents with anti-inflammatory effects in lemon also suggests the possibility of synergetic effects by different chemical compounds through the activations of separate receptors and channels.…”
Section: Chemical Constituents Of the Essential Oils Used In Olfactor...mentioning
confidence: 99%
“…Therefore, we propose that it is important to test other combinations of essential oils, especially the combinations of essential oils with chemical constituents with anti-inflammatory effects and with binding affinity to SARS-CoV-2. For example, bitter orange, cinnamon, cypress, elderberry, geranium, lavender, lemongrass, licorice, mint, oregano, paper mulberry, peppermint, summer savory, tea tree, tea plant, thyme, and turmeric contain chemical constituents with binding affinity to SARS-CoV-2 as well as these with anti-inflammatory effects ( Koyama et al, 2021 ). There are two major targets that the binding takes place.…”
Section: Chemical Constituents Of the Essential Oils Used In Olfactor...mentioning
confidence: 99%
See 1 more Smart Citation